OPINION OF MUSLIM STUDENTS IN FACULTY OF MEDICINE UISU IN 2017-2018 ABOUT USING ONLINE TRANSPORTATION DRIVER INTERPERSONAL COMMUNICATION TO PRODUCE SERVICE USER SATISFACTION - Mailin Mailin; Zulfan Kurniadi (Almufida : Jurnal Ilmu-Ilmu Keislaman, 2022)
Interpersonal communication or interpersonal communication in communication studies is defined as the process of exchanging information between two or three people, as this communication event occurs a lot in everyday life, both in schools, offices and in-service events such as Grab-Car drivers with consumers or service users. Changes that occur in the world of transportation have indeed attracted the attention of various parties, including the presence of transportation that is integrated with the application of communication technology. This research was conducted quantitatively, namely research that describes or explains a problem whose results can be generalized. This study produces quantitative data, namely data obtained from written respondents who were examined from questionnaires. The location of this research is the Faculty of Medicine, UISU Medan, North Sumatra. Measurement of the effectiveness of a communication process can be seen from the achievement of the goals of the sender of the message from the service seller and service user. The impression is the result of delivering the communicator's message to the communicant which will produce a good or bad impression. Happy is the peak of pleasure which is considered to be able to describe satisfaction after the achievement of all opinions from the satisfaction of service users. Happy will also generate a sense of trust and satisfaction for someone, and can continue to using Grab-Car if Service users feel happy every time, they travel.